The role of social media in promoting sustainable green lifestyles: Influencers and value co-creation with Gen Z in Indonesia - Suryaputra, Rizky; Daryanti, Sri; Setyowardhani, Hapsari (Journal of Entrepreneurial Economics, 2024)
This study investigates the impact of social media on encouraging environmentally friendly behaviors among Generation Z individuals in Indonesia. The study specifically examines the influence of social media influencers and the collaborative production of value. Background: Generation Z exhibits a strong level of involvement with digital platforms, which significantly impact their environmental consciousness and actions. Prior study emphasizes the significance of social media in influencing environmentally conscious behaviors, however there is a lack of extensive investigation on this subject specifically in the Indonesian setting. Methods: A total of 263 respondents provided data using self-administered surveys sent via Line, WhatsApp Group, and Instagram. The study employed regression analysis to investigate the associations among social media engagement, value co-creation, and the adoption of sustainable green lifestyles. Finding: The findings suggest that social media has a substantial impact on individuals' intentions to make environmentally friendly purchases and their level of awareness regarding environmental issues. Influencers are particularly important in spreading information about sustainability. Value co-creation promotes active involvement of the community, leading to a stronger dedication to sustainable practices. Conclusion: These findings offer useful insights for policymakers, educators, and marketers to effectively employ social media in promoting environmental sustainability in Indonesia.